MOTIVASI PETANI MENANAM CABE (Capsicum Annum L) DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2016)
Background of this research is motivation of farmer chili plant of land prepation, production, and price in chili plant process and the purposes for obtain information, analyze and discuss about motivation of farmer chili plant in Lembah Gumanti Subdistrict Solok Regency.Kinds of the research used qualitative research. The informant used snowball sampling is accumulation sample technique beginning small quantity, then large ther informant in thisresearch is society a chili plant. Technique of collect data used observation, interview and documentation. Technique of data analysis is reduction data, data display and verification. Research findings are 1) The motivasion of farmer chili plant see from land preparation don’t difficult very motivate the farmer in chili plant, the farmer not load although obstaste for land preparation for chili plant. 2) The motivation of farmer chili plant see from productionlevel the advance very motivate farmer in chili plant, until increase farmer income and need fill every day. 3) The motivasion of farmer chili plant see from chili price a high very motivate farmer in chili plant, until increase economy ability farmer chili plant in Galagah.Keyword : motivation, farmer chili plant